SURVEI TINGKAT KEDISIPLINAN SISWA PADA PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DI SMP N 2 SEDAYU - Dyas Genta; Dody Tri Iwandana (Program Studi Pendidikan Jasmani, Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dharmas Indonesia, 2023)
study used a descriptive method. The subject of this study was a PJOK teacher at SMP Negeri 2 Sedayu. Data collection was carried out using observation, interview, and documentation methods. If there is no discipline, it will be an obstacle for teachers in carrying out learning activities in theory and practice in PJOK learning. The purpose of this study was to determine the picture of student discipline at SMP Negeri 2 Sedayu. From the results of student discipline research in PJOK learning at SMP Negeri 2 Sedayu, it is quite disciplined in applying the discipline that exists in PJOK learning both in theory and practice. This study concluded that developing a disciplinary module needs to be applied to teachers of SMP Negeri 2 Sedayu.